2014
DOI: 10.1007/s40618-014-0180-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in adolescents with Turner syndrome is comparable to obese peers, but the overall metabolic risk is lower due to unknown mechanism

Abstract: Insulin resistance in adolescents with TS on growth hormone treatment is comparable to Ob patients, but overall metabolic risk factors seem to be lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Patients with ovarian dysgenesis due to TS have an increased risk of metabolic disorders, including insulin resistance and diabetes [42,43]. Elevated cholesterol levels in childhood promote the onset of atherosclerosis in adulthood [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ovarian dysgenesis due to TS have an increased risk of metabolic disorders, including insulin resistance and diabetes [42,43]. Elevated cholesterol levels in childhood promote the onset of atherosclerosis in adulthood [44].…”
Section: Discussionmentioning
confidence: 99%
“…The development of insulin resistance is influenced by body weight, body composition and karyotype [47,48]. It has been shown that normal-weight women with TS have a lower metabolic risk, potentially related to Fibroblast Growth Factor 21 (FGF 21) metabolism [42]. FGF21 significantly influences metabolism by enhancing insulin sensitivity, regulating glucose uptake, promoting lipid metabolism, increasing energy expenditure, and inducing the browning of white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests the possible participation of obesity and HRT by analogy to the results of research conducted in various groups of patients (4). As women with TS have short stature and abnormal body proportions, they are more likely to be overweight and obese (4,17,18,19,30). In our present study, no relationship was found between obesity and LFTs.…”
Section: Discussionmentioning
confidence: 99%
“…Because of short stature and abnormal body proportions, women with Turner syndrome are more likely to be overweight and obese. However, metabolic disorders such as impaired insulin sensitivity, hypercholesterolemia, and liver steatosis are often diagnosed even in non-obese ones [21, 22]. Some data point that metabolic disturbances may be associated with the origin of the X chromosome monosomy itself.…”
Section: Discussionmentioning
confidence: 99%
“…Also insulin resistance is thought to be connected not only with body weight and composition but also with the karyotype [23]. As it was recently shown in survey, overall metabolic risk in normal-weight women with Turner syndrome is lower than in obese peers and some other mechanisms, e.g., FGF 21 may play an important role in this phenomenon [22]. The influence of growth hormone treatment and estrogen replacement on metabolism of patients with TS is significant.…”
Section: Discussionmentioning
confidence: 99%